INNOVATIVE POTENTIAL OF THE ORGANIZATION AS A COMPETITIVE FORCE OF «ELENA FURS» FACTORY - N. Maslennikova; A. Petrosian (Вестник университета)
The purpose of the article consists in the choice of the approach to the assessment of the innovative potential of the organization, since the quality of the assessment of innovation potential becomes the basis of the strategy of innovation transformation. Each approach is tested on the example of the fur factory «Elena Furs» and the feasibility and validity of the assessment of the innovative potential of the organization is checked. The article contains calculations confirming the availability of innovative capacity in the organization, but the use of these approaches did not allow us to identify specific areas for its development. The estimation of innovative potential from positions of competitive force in the external environment is offered that will allow to compare innovative potential with potential of participants of an environment and to develop strategic directions of development of innovative potential in the field of new technologies of production, marketing, personnel management, etc.